2021
DOI: 10.1093/fampra/cmaa142
|View full text |Cite
|
Sign up to set email alerts
|

Lessons for the global primary care response to COVID-19: a rapid review of evidence from past epidemics

Abstract: Background COVID-19 is the fifth and most significant infectious disease epidemic this century. Primary health care providers, which include those working in primary care and public health roles, have critical responsibilities in the management of health emergencies. Objective To synthesize accounts of primary care lessons learnt from past epidemics and their relevance to COVID-19. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 52 publications
(140 reference statements)
2
72
0
5
Order By: Relevance
“…Coordination between primary care and other parts of health system at the frontline of an epidemic is essential [23] . Yet in some European countries, primary care collaboration outside of an emergency is not a common feature in their health systems.…”
Section: Discussionmentioning
confidence: 99%
“…Coordination between primary care and other parts of health system at the frontline of an epidemic is essential [23] . Yet in some European countries, primary care collaboration outside of an emergency is not a common feature in their health systems.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies such as strengthening the primary healthcare system and providing coordinated with reliable information to the physicians were essential. 18 29 30 The innovative CHCG comprehensive primary healthcare system model was developed in Taiwan after the previous SARS outbreak and the disastrous 921 earthquake. These conditions created an awareness of the need to reinforce primary care under the tremendous public health threats.…”
Section: Discussionmentioning
confidence: 99%
“…As the unprecedented pandemic threat persists over a broad range of medical care, it is of paramount importance to understand and optimise the primary healthcare workforce, and to maintain sufficient frontline physicians. [15][16][17][18] However, previous reports revealed a high susceptibility to infection among healthcare workers because more than 3000 healthcare workers have been infected in China and 20% of responding healthcare workers were infected early in the COVID-19 pandemic in Italy. 19 20 Moreover, a systematic review by Kisely et al 21 revealed that healthcare workers who had direct contact with patients had higher levels of both acute and posttraumatic stress and psychological distress.…”
Section: Introductionmentioning
confidence: 99%
“…A system of primary care performance measurement that meets the information needs of the public, governments and ministries of health, regional health authorities, local communities and primary care practices and organizations for the purposes of public reporting, accountability, planning, and quality improvement. Health IT that effectively supports patients and providers through decision support tools for clinicians and patients, support for patient selfmanagement, performance measurement and reporting capacity and interconnectivity for information exchange across health-care settings [31].…”
Section: Framework For Advancing Improvement In Primary Care Nursesmentioning
confidence: 99%